KURIKULUM MUATAN LOKAL KEAGAMAAN DALAM PEMBENTUKAN BUDAYA RELIGIUS - Fatikah, Noor; Nafi’ah, Nurul (ILJ: Islamic Learning Journal, 2023)
The lokal content curriculum is a set of plans and arrangements regarding the content and learning materials specified by the regions according to the conditions and needs of each region and the methods used as guidelines for the implementation of teaching and learning activities. Whereas religius culture is the realization of religius teaching values as traditions or habits in behavior that are followed by all students. So the implementation of Religius Lokal Content lessons will be able to provide a function as a moral and ethical foundation in all activities, both in the context of school and in society at large. generally. This study aims to determine the learning model of lokal religius content and the implementation of Kasagamaan lokal mustan learning in the formation of religius culture at SMPN 2 Mojowano Jombang. This research is a qualitative field research. . Furthermore, data analysis was carried out using descriptive qualitative analysis. The results showed that 1) Religius Lokal Content Learning Model at SMP Negeri 2 Mojowamo a) Using learning modules. b) Using RPP (Learning Experience Plan) c) Learning Methods of Lokal Religius Content d) Evaluation of learning. 2) Implementation of Religius Lokal Mustan Learning in Forming Religius Culture of students at SMP Negeri 2 Mojowamo a) Routine habit b) Duhur congregational prayer c) Duha prayer d) Spiritual motivation d) Visiting a friend who is sick